2021
DOI: 10.12790/ahm.21.0097
|View full text |Cite
|
Sign up to set email alerts
|

History and Recent Advances in Microsurgery

Abstract: Since the late 19th century, microsurgery has achieved many miracles in history of surgery. With the development of microsurgical instruments and techniques, especially the first operating microscope invented by Carl Zeiss in 1953, the limitations steadily decreased and finally reached a limitless level of today’s supermicrosurgery. The chronological history of microsurgery can be divided into four periods: the beginning period of the late 19th to early 20th century when the essential microsurgical tools and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…This can make it difficult for them to focus, and over time, the cervical spine may develop degenerative changes. 10 11 12 13 In our study, the surgeon has reported positive experiences regarding head and neck ergonomics while using the RS, which is consistent with the literature. Hence, especially in surgeons with high operating caseloads, display-based exoscopes might play a significant role in avoiding WMDs.…”
Section: Discussionsupporting
confidence: 90%
“…This can make it difficult for them to focus, and over time, the cervical spine may develop degenerative changes. 10 11 12 13 In our study, the surgeon has reported positive experiences regarding head and neck ergonomics while using the RS, which is consistent with the literature. Hence, especially in surgeons with high operating caseloads, display-based exoscopes might play a significant role in avoiding WMDs.…”
Section: Discussionsupporting
confidence: 90%
“…Malt was the first to disclose upper extremity replantation in 1962 and significant advances have been made since then. 1 According to the most recent findings, re-implantation is performed in around 15% of upper extremity amputation cases, with a success rate usually over 70%. 4 The case report presented here describes a rare case of a successful re-implantation in a patient with a persistent median artery as the main blood supply to the hand, no ulnar artery and absent superficial and deep palmar arches.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous severed body parts have, however, been successfully surgically restored since Komatsu and Tamai reported the first successful re-implantation of the thumb in 19,68. 1 Surgical methods have advanced significantly in the limb reimplantation, enhancing functional restoration and quality of life.…”
Section: Introductionmentioning
confidence: 99%